2021
DOI: 10.1111/trf.16637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rotational thromboelastometry–guided transfusion management in patients undergoing surgical intervention for postpartum hemorrhage: An observational study

Abstract: Background: Postpartum hemorrhage (PPH) can be associated with coagulopathy, which may be difficult to rapidly assess and may exacerbate blood loss. Rotational thromboelastometry (ROTEM) at the point of care can guide clinician choice of blood products and has been shown in some settings to reduce transfusions and improve outcomes. This hospital-based observational study aims to measure effects of a ROTEM-guided transfusion protocol on transfusion practice and clinical outcomes in patients with PPH managed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(68 reference statements)
0
3
1
Order By: Relevance
“… 30 , 31 , 32 , 33 On the contrary, a recent observational study reported no benefit of ROTEM with regard to RBC transfusion in PPH. 39 However, in our study a small but statistically relevant difference in median total blood loss in favour of the ROTEM group was seen. Whether this is a result of more efficient haemostatic resuscitation is uncertain.…”
Section: Discussioncontrasting
confidence: 65%
“… 30 , 31 , 32 , 33 On the contrary, a recent observational study reported no benefit of ROTEM with regard to RBC transfusion in PPH. 39 However, in our study a small but statistically relevant difference in median total blood loss in favour of the ROTEM group was seen. Whether this is a result of more efficient haemostatic resuscitation is uncertain.…”
Section: Discussioncontrasting
confidence: 65%
“…We included Four cohort studies[ 19 27 28 29 ] and one randomized clinical trial[ 30 ] out of 251 identified publications in this review after satisfying the inclusion criteria. Six ongoing clinical trials (ClinicalTrials.gov) were excluded as their result is still awaited [ Figure 1 and Table 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 18 ] However, extrapolating these results to PPH patients might lead to complications like allergy and lung injury. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…Tsang et al also compared PPH management before and after adoption of ROTEM in 900 women with estimated primary PPH >500 mL required management in the operating theater after vaginal delivery or >750 mL after caesarean delivery. 91 The mean total blood loss was 1,243 mL and only 32% of eligible patients received a ROTEM test, predominantly because the bleeding had stopped. The group did not observe a change in RBC transfusion or reduced cost of PPH treatment, but did show a reduction in platelet and FFP transfusion.…”
Section: Evidence That Poc-vha Algorithms Improve Pph Outcomesmentioning
confidence: 99%